2019
DOI: 10.1155/2019/5016483
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin Inhibits Renal Cancer Growth by Downregulating MicroRNA-21 through the Activation of YAP1

Abstract: Renal cell carcinoma (RCC) is the second most common human urinary tumor. Eupatilin is the main active ingredient of the traditional Chinese medicine Artemisia asiatica. The effect of Eupatilin on RCC and the underlying mechanism remain unknown. Here, we investigated the anticancer effects and mechanisms of Eupatilin in RCC in vivo and in vitro, laying an experimental foundation for the clinical application of Eupatilin in the treatment of RCC. The results showed that Eupatilin significantly inhibited 786-O ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Tan et al [21] found that the incidence of side effects in places such as cardiovascular system and digestive system in patients treated with traditional Chinese medicine was significantly lower than that of the single western medicine treatment when patients were treated after radical resection of RCC with TCM on the basis of basic western medicine treatment. Zhong et al [22] found that combined Chinese medicine therapy was more stable for patients with renal cancer after laparoscopic radical resection and prolonged survival time. In this study, Danggui Beimu Kushen Pills combined with interferon were used to treat patients after RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [21] found that the incidence of side effects in places such as cardiovascular system and digestive system in patients treated with traditional Chinese medicine was significantly lower than that of the single western medicine treatment when patients were treated after radical resection of RCC with TCM on the basis of basic western medicine treatment. Zhong et al [22] found that combined Chinese medicine therapy was more stable for patients with renal cancer after laparoscopic radical resection and prolonged survival time. In this study, Danggui Beimu Kushen Pills combined with interferon were used to treat patients after RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with eupatilin in the xenograft mouse model for esophageal cancer inhibits the activity of AKT and ERK1/2 in tissues [9]. Moreover, a recent study showed that eupatilin can target microRNAs in cancer cells to induce apoptosis, so further studies are needed to determine if eupatilin may have anticancer effects by modulating microRNAs in ovarian cancer cells [28]. Accumulated evidence suggests that eupatilin inhibits cell proliferation and induces apoptosis as a common mechanism in various cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that quercetin and quercetin 3-O-glucuronide regulate the sleep-wake cycle by activating the GABA(A) receptor and improving sleep duration and quality of insomnia mice ( Kambe et al, 2010 ; Kim et al, 2021 ). Eupatilin has been shown to inhibit pancreatic cancer cells, the growth of kidney cancer cells, and the metastasis of prostate cancer cells while improving the immune system ( Zhong et al, 2019 ; Serttas et al, 2021 ; Park and Kim, 2022 ). Our study first reports that eupatilin may improve sleep of a sleep-disturbed zebrafish, but it requires further investigation.…”
Section: Discussionmentioning
confidence: 99%